Systematic Review of the Relation Between Intestinal Microbiota and Toll-Like Receptors in the Metabolic Syndrome: What Do We Know So Far? - Portela-Cidade,José Pedro (2015)
Introduction: Metabolic syndrome is an emerging problem in developed countries and presents itself as a potential threat worldwide. The role of diabetes, dyslipidaemia and hepatic steatosis as pivotal components of the metabolic syndrome is well known. However, their common persistent chronic inflammation and its potential cause still elude. This systematic review aims to present evidence of the mechanisms that link the intestinal microbioma, innate immunity and metabolic syndrome. Methods: A comprehensive research was made using PubMed database and 35 articles were selected. Results: We found that metabolic syndrome is associated to increased levels of innate immunity receptors, namely, Toll-like receptors, both in intestine and systemically and its polymorphisms may change the risk of metabolic syndrome development. Microbioma dysbiosis is also present in metabolic syndrome, with lower prevalence of Bacteroidetes and increased prevalence of Firmicutes populations. The data suggest that the link between intestinal microbiota and Tolllike receptors can negatively endanger the metabolic homeostasis. Conclusion: Current evidence suggests that innate immunity and intestinal microbiota may be the hidden link in the metabolic syndrome development mechanisms. In the near future, this can be the key in the development of new prophylactic and therapeutic strategies to treat metabolic syndrome patients.